Dams of Ecuador - Nieto, Luis Marín (Revista Universidad de Guayaquil, 1987)
This work presents preliminary information on the problems of planning, design, construction and behavior of dams built in Ecuador during this century. This work corresponds to some chapters, as a synthesis of a book that the author is preparing called DAMS OF ECUADOR in the process of preparation.